Physicochemical characteristics of hazardous sludge from effluent treatment plant of petroleum refinery as feedstock for thermochemical processes - Singh B.; Kumar P. (My University, 2025)
The physicochemical characteristics of hazardous petroleum sludge (PS) become reasonably important when it used as feedstock in thermochemical processes for energy generation. Present work aimed at investigating the physicochemical characteristics of PS before and after soxhlet extraction. The soxhlet extraction was performed using petroleum ether, hexane, toluene, and benzene as solvent, among which hexane yields maximum amount of liquid. Therefore, PS before and after solvent extraction using hexane was characterized using proximate, ultimate, TGA/DTG/DTA, FTIR, XRD, and SEM-EDX analyses, while liquid extracted from PS was characterized by GC–MS analysis. Results revealed that moisture and volatile matter of PS decreased from 23.31 to 9.98 wt % and 65.10 to 62.71 wt %, respectively, while fixed carbon increased from 9.16 to 23.21 wt % after soxhlet extraction. Thermogravimetric analysis (TGA) suggested four distinctive zones during thermal decomposition of PS. Kinetic triplets (activation energy, frequency factor, order of reaction) for major devolatilization zone of organic compounds for raw and filtered PS was found to be 27.80 kJ/mol, 63.802 min−1, 0.07 and 35.01, 272.91, 0.11, respectively. TGA indicated that sludge can be processed by pyrolysis in the temperature range of 250–650 . Many value added chemicals were identified in liquid extracted from PS among which phytol (50.72 %) was the most abundant. © 2020 Elsevier Ltd. All rights reserved.